IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS (MBG) DAN DAMPAKNYA TERHADAP MOTIVASI BELAJAR SISWA UPT SDN 4 GADINGREJO - Dwi Hardiyani; Apri Wahyudi; Muhammad Mona Adha (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) and its impact on students’ learning motivation at UPT SD N 4 Gadingrejo. This research employs a qualitative approach with a descriptive research design, focusing on an in-depth understanding of the program implementation process and its influence on learning activities. The research subjects include the principal, classroom teachers, students, and parties directly involved in the implementation of the MBG program, selected using purposive sampling techniques based on specific considerations. Data were collected through observation, interviews, and documentation to obtain comprehensive information. Data validity was ensured through source triangulation and technique triangulation, while data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the MBG program has a positive impact on students’ learning motivation, such as increased learning concentration, student activeness in class, enthusiasm for attending school, and participation in the learning process. In addition, the program also strengthens positive social interactions among students. The success of the program is supported by good coordination between the school and implementing parties, although several technical constraints are still encountered in its implementation.